Odpowiedzi

2009-12-08T14:22:01+01:00
(√2+√3)(√6+√3)=√12+√18+√6+3=2√3+3√2+√6+3
(x√2+1)(x-2√2)=x²√2+x-4x-2√2=x²√2-3x-2√2
(x+√2)(2√2+x)=2√2x+4+x²+√2x=x²+3√2x+4
(x+√5)(x-√5)=x²-5
(2y-√3)(y+1)= 2y²-√3y+2y-√3
2009-12-08T14:28:55+01:00
(√2+√3)(√6+√3)=√12+√6+√18+3= 2√3+ √6+ 3√2+ 3

(x√2+1)(x-2√2)=x²√2+x-4x-2√2= x²√2- 3x- 2√2

(x+√2)(2√2+x)=2x√2 + 4 + x²+ x√2= x²+ 3x√2 +4

(x+√5)(x-√5)= x²-5

(2y-√3)(y+1)= 2y²- + 2y - y√3 - √3
2009-12-08T15:41:16+01:00
(√2+√3)(√6+√3)=√12+√18+√6+3=2√3+3√2+√6+3
(x√2+1)(x-2√2)=x²√2+x-4x-2√2=x²√2-3x-2√2
(x+√2)(2√2+x)=2√2x+4+x²+√2x=x²+3√2x+4
(x+√5)(x-√5)=x²-5
(2y-√3)(y+1)= 2y²-√3y+2y-√3
musisz jakżą liczbę pomnożyć przed nawiast chyba tak juz dawno to mialam